Design, synthesis and biological evaluation of novel 1H-pyrazole-4-carbonyl-4, 5, 6, 7-tetrahydrobenzo [b]thiophene derivatives as gut-selective NaPi2b inhibitors. (1st March 2022) - Ushiki, Yasunobu; Kawabe, Kenichi; Yamamoto-Okada, Kumiko; Uneuchi, Fumito; Asanuma, Yuta; Yamaguchi, Chitose; Ohta, Hiroshi; Shibata, Tsuyoshi; Abe, Tomohiro; Okumura-Kitajima, Lisa; Kosai, Yuki; Endo, Mayumi; et al.
Graphical abstract: Abstract: Intestinal sodium-dependent phosphate transport protein 2b (SLC34A2, NaPi2b) inhibitors are expected to be potential new candidates for anti-hyperphosphatemia drugs. However, a risk of on-target side effects based on the inhibition of NaPi2b in the lung and testis has been reported. To identify gut-selective (minimally systemic) NaPi2b inhibitors, we prepared and evaluated 1H-pyrazole-4-carbonyl-4, 5, 6, 7-tetrahydrobenzo[ b ]thiophene derivatives with highly polar functional groups to reduce systemic exposure. As a result, compounds 36a and 36b showed a good activity in vitro and a low bioavailability in Sprague-Dawley (SD) rats. However, these compounds did not suppress phosphate absorption in SD rats. This lack of in vivo efficacy could be due to the high hydrophobicity of these compounds. The results of further investigations of other classes of compounds with appropriate physical properties will be reported in due course.